Development and Validation of an Aerobic Exercise Adherence Questionnaire for Female College Students - Poppy Elisano Arfanda; Ians Aprilo; M. Adam Mappaompo; Arimbi Arimbi (Education and Talent Development Center Indonesia (ETDC Indonesia), 2026)
Exercise adherence is a crucial factor in the success of an aerobic dance program; however, valid and reliable measurement instruments to evaluate this compliance among college students remain limited. This study aims to test the psychometric properties of an exercise adherence questionnaire for aerobic dance programs specifically tailored for college students. The study employed a descriptive quantitative approach with an instrument validation study design. The research subjects consisted of 30 female college students who regularly participated in an aerobic dance program. The research instrument was a workout adherence questionnaire consisting of 18 statements with a five-point Likert scale, covering five main dimensions: exercise motivation and commitment, comfort and enjoyment, perceived benefits of exercise, sustainability and consistency, and barriers and time management. Validity testing was carried out using Pearson Product Moment correlation, while reliability testing was analyzed using Cronbach's Alpha coefficient. The analysis results showed that all 18 statement items were declared construct valid, with calculated r values ranging from 0.568 to 0.745, which all exceeded the r table value of 0.361 at the 0.05 significance level, with the highest indicator representation in the perceived benefits of exercise dimension. Furthermore, the instrument demonstrated very stable internal consistency with a Cronbach's Alpha coefficient of 0.862, categorized as high reliability. Consequently, this questionnaire proved adaptive to the unique characteristics of aerobic exercise as a rhythmic and dynamic group sport, providing a valid, objective, and reliable assessment tool that is highly recommended for use by researchers and exercise practitioners to evaluate program adherence in the future.